Model Pembelajaran Trade a Problem: Peningkatan Kemampuan Representasi dan Pemecahan Masalah Matematis - Fadila, Abi; Fredi Ganda Putra; Karunia Akbar Permata; Riyama Ambarwati (Institut Agama Islam Negeri Curup, 2024)
This research aims to analyze the influence of the Trade a Problem Cooperative Learning Model on students' representation and problem-solving abilities at SMPN 1 Abung Pekurun. The research method used is Quasi Experimental Design with data collection in the form of tests on samples of classes 7C and 7D for the 2023/2024 academic year. This research found that the Trade a Problem Model had a significant influence on each dependent variable with p-value = 0,000 so that p-value meaning was rejected. The posttest average for the mathematical representation ability of the experimental class was 88 while the control was 76. In terms of mathematical problem-solving ability, the posttest average for the experimental class was 87 while the control was 74. So, the results of the study showed that: 1) there is an influence of the Trade a Problem Learning Model on mathematical problem-solving ability and mathematical representation abilities; 2) there is an influence of the Trade a Problem Learning Model on mathematical problem-solving abilities; and 3) there is an influence of the Trade a Problem Learning Model on mathematical representation abilities. Trade a Problem Model can be used as an effective alternative to improve students' mathematical problem-solving and representation abilities.